Nursing Students Challenges in Studying While Working in The Era of The Covid-19 Pandemic: a Qualitative Focus Group Study - Ellen Ruth Tambunan Tambunan; Evelyn Hemme Tambunan (Jurnal Gema Keperawatan, 2022)
Studying while working in the era of the Covid-19 pandemic has become a challenging experiences among nursing students. Various experiences in such positive and negative experiences as well as challenging experiences in online learning were the themes of several qualitative research results. This study aim to investigate the nursing students challenges in studying while working in the era of the Covid-19 pandemic. Two focus-group interviews were conducted with 17 participants (age 40-60 years) who have working experience as a nurse more than 10 years in an extension nursing program at one of private nursing school in Bandung, Indonesia. Trustworthiness was established by Moser and Korstjens criteria. Then, the qualitative inductive content analysis was performed. Four themes were generated namely time challenges, technology challenges, individual challenges and learning challenges. There were ten sub-themes emerged namely studying and working at the same time, dividing time between studying, working and doing household chores, time and location difference, use of computer and zoom, internet network, age and length of time not in college, physical health, credits and many courses, lots of learning tasks and learning strategies. While there is a growing body of research on the online learning challenges in the era of Covid-19 pandemic, a need to continue to study it through thoughtful, well-designed studies to serve as a guide to scholars and educators in online learning and beyond.